ANALYSIS OF FINANCING NEEDS FISHERMAN AGAINST SHARIA BANKING STUDIES PELABUHAN RATU SUKABUMI JAWA BARAT - fadillah, atni; Kurnia, Tuti (NISBAH: JURNAL PERBANKAN SYARIAH, 2018)
Â The purpose of this study was to determine the condition of fishing economy of coastal areas Pelabuhan Ratu Beach Sukabumi, West Java including into condition of economic is prosperous or less prosperous, and analyzing financial products such as what is appropriate to meet the needs of fishermen, from daily necessities to the need to go to sea , The method used in this research is descriptive qualitative method. conclusions of this study is the economic condition of fishermen Pelabuhan Ratu still relatively less prosperous and have not been able to meet their needs, either daily needs as well as the need to go to sea. Islamic bank financing products accordingly to meet the financing needs of fishermen is using the murabaha contract.Keywords: Financing, Supplies, Fisherman